(untitled) (Journal of Philosophy Culture and Political Science, 2015)
In the article the idea of the unity of philosophical and pedagogical thinking of Kant, which follows from the Kantian moral and philosophical reflections. Education Kant – the formation of morality, preservation of autonomy and freedom. The starting point is the argument of Kant’s anthropological definition that only by educating people to become human. Kant organizes tasks of education: discipline, culture, civilization, introduction to civilization and morality in the sense of the categorical imperative. The measure of education – a subject that is configured to himself as a man who saves his freedom of independent thinking and thus your mind. The purpose of education – to direct the human race for excellence, facilitate the implementation of a man of his appointment, to cultivate their human nature